Analysis of Factors Affecting Company Management Follow the Amnesty Tax in KPP Madya Makassar - B. Burhanuddin (Golden Ratio of Taxation Studies, 2021)
This research was conducted with the aim of empirically testing the influence of knowledge, perceptions, tax authorities, benefits, and sanctions on the motivation of company management to participate in tax amnesty at the Office Makassar Middle Tax Service. The method used in this research is descriptive method with survey approach. The sample of this research is the management of companies registered with the Service Office Makassar Middle Tax. Sampling is done with the slovin formula. Methods of data collection is done by questionnaire spread live to management company as much 85 questionnaire. Data analyzed with using Multiple Linear Regression Analysis. The results of this study indicate that simultaneously variable knowledge, perceptions, tax authorities services, benefits and sanctions have a significant effect on motivation management company follow amnesty tax. Based on test Partial variables perception, and benefit, influential positive significant to motivation management company follow amnesty tax, but variables service has no significant positive effect on the motivation of company management to participate in tax amnesty , while the variable knowledge and sanctions have no significant negative effect on management motivation company follow tax amnesty .